Influence Evaluation of Buildings Constructed in Protected Zone on St.Petersburg Subway Underground Structures Stress-strain State. (2017) - Lediаev, A.P.; Konkov, A.N.; Novikov, A.L.; Soloviev, D.A.
Abstract: Building in protected zones of subway can seriously influence on stress-strain state and operational reliability of underground structures. It should be noted that till nowadays there are no normative documents which regulate the permissible additional load on various types of underground subway constructions, the grade of acceptable approaching of the foundations and piles elements and common attitude to protected area dimensions of different underground constructions and other important factors. There is practical need in developing of criterion of permissibility evaluation of ground construction in the St. Petersburg subway protected zone. The criterion depends on various factors: type of underground structures, geotechnical conditions, the current technical state of underground constructions, the allowed value of additional loads on them and other important factors. The article presents the algorithm for the influence evaluation of ground construction on underground structures as well as the example of its practical realization during developing the design solutions and during construction. There are examples of realization of proposed methodology for influence evaluation of ground construction on various St. Petersburg metro underground constructions.